Skin findings in overweight and obese individuals - Nazik, Hulya; Kokcam, Ibrahim; Demir, Betul; Gul, Feride Coban (Turkish Soc Dermatology Venerology, 2016)
Background and Design: The aim of the present study was to compare dermatoses detected in overweight and obese individuals with the data obtained from individuals with a body mass index (BMI) below 25.0 kg/m(2) and to emphasize the effects of obesity on skin health. Materials and Methods: The study was performed with 510 volunteer participants aged above 18 years, who attended the dermatology outpatient clinic. 150 normal-weight individuals with a BMI below 25.0 kg/m(2) constituted the control group, 130 individuals with BMI between 25.0 and 29.9 kg/m(2) constituted the overweight group, and 230 individuals with BMI above 30.0 kg/m(2) constituted the obese group. A detailed dermatological examination was performed and the data was recorded. Results: A total of 510 participants, 194 males and 316 females, were included in the study. The mean age of the subjects was 32.05 +/- 10.9, 44.91 +/- 13.4, and 39.78 +/- 16.4 in the control, overweight, and obese groups, respectively. The most common dermatosis in the overweight and obese groups was striae distensae in 316 individuals (62%), plantar hyperkeratosis in 249 (48.8%), dystrophic cellulitis in 216 (42.4%), acrochordon in 204 (40%), acanthosis nigricans in 135 (26.4%), varicose veins in 134 (26.3%), and keratosis pilaris in 108 individuals (21.2%). Conclusion: Several dermatoses are more frequently seen in obese and overweight individuals due to insulin resistance and mechanical effects when compared with normal-weight individuals.
Aşiri kilolu ve obezlerde deri bulgulari
Keywords: Obesity; overweight; dermatose; sex